Dechristianisierung und Rechristianisierung: Der deutsche Katholizismus im europäischen Vergleich - Holzem, Andreas (Kirchliche Zeitgeschichte, 1998)
The processes of decristianisation and secularisation amongst German Catholics, as well as any possible rechristianisation in a Catholic sense, have to be seen in a wider European setting. For such developments can only be understood in the context of the Catholic milieu which dominated church life from the mid-19th to the mid-20th century, and which itself was a product of the kind of "confessionalisation" of the late 16th and 17th centuries, and the related forms of resistance to secularisation. It is clear that one must examine the connections between the erosion of the milieu and the advance of secularisation, as also the self-understanding of German Catholics as being the victims of modernisation. This will provide some indicators for the likelihood of rechristianisation.